2021
DOI: 10.1002/fsn3.2167
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of tangeretin and heptamethoxyflavone on obese C57BL/6J mice fed a high‐fat diet and analyses of the metabolites originating from these two polymethoxylated flavones

Abstract: Two compounds from citrus peel, tangeretin (TAN) and 3′,4′,3,5,6,7,8‐heptamethoxyflavone (HMF), were investigated for their abilities to repair metabolic damages caused by an high‐fat diet (HFD) in C57BL/6J mice. In the first 4 weeks, mice were fed either a standard diet (11% kcal from fat) for the control group, or a HFD (45% kcal from fat) to establish obesity in three experimental groups. In the following 4 weeks, two groups receiving the HFD were supplemented with either TAN or HMF at daily doses of 100 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
(96 reference statements)
1
5
0
Order By: Relevance
“…Compared to the current experiment, these doses were 4.6 to 9.1 times higher, the initial body weight was 50% higher and, the intervention was longer (6 wk). In contrast, Nery et al [27] found similar results to the current study in mice fed a highfat diet plus 100 mg/kg bw TAN for 4 weeks. The authors showed an increase in weight gain compared to the standard diet, but no change in animals fed a high-fat diet without TAN.…”
Section: Discussionsupporting
confidence: 79%
“…Compared to the current experiment, these doses were 4.6 to 9.1 times higher, the initial body weight was 50% higher and, the intervention was longer (6 wk). In contrast, Nery et al [27] found similar results to the current study in mice fed a highfat diet plus 100 mg/kg bw TAN for 4 weeks. The authors showed an increase in weight gain compared to the standard diet, but no change in animals fed a high-fat diet without TAN.…”
Section: Discussionsupporting
confidence: 79%
“…The result shows that the blood serum glucose levels, leptin, resistin, and TBARS in these diabetic mice were considerably lower after four weeks of supplementation with 100 mg/kg b.w. of tangeretin than in the healthy control and non-supplemented HFD groups [43]. Shin et al 2017 examined the effects of tangeretin on inflammatory changes and glucose absorption in a coculture of RAW 264.7 cells (a mouse macrophage cell line) and 3T3-L1 adipocytes (a mouse adipocyte cell line), whereby they observed that tangeretin (100 µM) treatment reduced the expression of interleukin IL-6, TNF-α and IL-1, inducible nitric oxide synthase, and cyclooxygenase-2 as well as the synthesis of nitric oxide, and also increase in glucose absorption in the coculture was observed.…”
Section: Mechanism Of Action Of Tangeretin Against Diabetes and Its R...mentioning
confidence: 77%
“…In C57BL/6J mice with pre-existing obesity, Marina et al [43] looked into the ability of tangeretin to restore metabolic damage brought on by a high-fat diet (HFD). The result shows that the blood serum glucose levels, leptin, resistin, and TBARS in these diabetic mice were considerably lower after four weeks of supplementation with 100 mg/kg b.w.…”
Section: Mechanism Of Action Of Tangeretin Against Diabetes and Its R...mentioning
confidence: 99%
“…In addition, the metabolite of nobiletin, 3′,4′-dihydroxy-5,6,7,8-tetramethoxyflavone, reduced LDL oxidation and attenuated the differentiation of monocytes to macrophages and diminished the uptake of modified LDL by macrophages ( 27 ). Both tangeretin and heptamethoxyflavone reduced lipid peroxidation (TBARS) in the serum of HFD mice and had a significant therapeutic effect on obesity and hyperlipidemia ( 28 30 ). Furthermore, some PMFs from Citrus peel regulate lipid homeostasis via suppressing multiple scavenger receptors ( 25 , 31 33 ).…”
Section: Introductionmentioning
confidence: 99%